Do Green Accounting Practices And Environmental Performance Enhance Firm Value ? Evidence From Profitability As A Moderating Factor (A Case Study Of Manufacturing Companies Listed on the Indonesia Stock Exchange, 2020–2024) - Vega Nurhaliza; Vicky Dzaky Cahaya Putra (LP2M IAIN Palopo, 2026)
This study aims to analyze the influence of Green Accounting and Environmental Performance on Company Value with Profitability as a moderation variable. The study uses a quantitative approach with a causal-associative design. The research sample consisted of 16 manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2020–2024, which were selected using the purposive sampling method so that 80 observational data were obtained. Green Accounting is measured through environmental cost disclosure, environmental performance is measured using PROPER ratings, profitability is measured by Net Profit Margin (NPM), and company value is measured using Tobin's Q. Data analysis is performed using multiple linear regression and Moderated Regression Analysis (MRA) with the help of IBM SPSS version 27. The results of the study show that Green Accounting has a positive but insignificant effect on the company's value while environmental performance has a negative and significant effect on the company's value. In addition, profitability has no significant effect on the company's value. The results of the moderation test show that profitability is not able to moderate the influence of Green Accounting and environmental performance on company value. These findings indicate that the company's sustainability practices have not been fully responded to by the Indonesian capital market as a factor that increases the company's value. This research supports the theory of legitimacy, which states that companies' efforts to gain social legitimacy have not always been followed by an increase in the company's value.